DINAMIKA UPAYA ADAPTIF DAN KEBERLANJUTAN UMKM KERAJINAN BAHAN ALAM DI KOTA SEMARANG PADA MASA PANDEMI - Berta Bekti Retnawati; Marlon Leong; Bernadeta Irmawati (Journal of Management Small and Medium Enterprises (SMEs), 2021)
The economic downturn due to the pandemic requires MSMEs, including natural handicrafts to survive. The purpose of this research is to examine the conditions in the field of adaptive efforts carried out by natural handicraft MSMEs to manage the situation in the midst of a pandemic as a means of surviving in this difficult situation. In-depth interviews with natural handicraft SMEs in Semarang City, conducted on 20 business owners with random sampling method and convenience sample. MSMEs that can adapt to situations by making innovative efforts and keep up with market demands are quite resilient. Adaptability can be made through products that are made and by means of marketing using e-commerce platforms and social media to approach and expand the target market. On the other hand, MSMEs that are not ready and stuttering in the adaptation process experience difficulties in responding to the changes and challenges that exist. The number of respondents and the limited variety of types of natural handicrafts, can still be explored more widely in a larger area. Provides an overview of the existing conditions in the empirical situation, especially natural handicraft MSMEs and provides input for policy makers to hasten to accelerate efforts to keep MSMEs able to exist through the difficult situation of the Covid-19 pandemic Keywords : SMEs, Adaptive, Pandemic